1973
DOI: 10.1159/000240538
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Intake on Maternal Milk Electrolytes and Aldosterone, Corticosterone and 18-Hydroxydeoxy-corticosterone Production in the Offspring of Rats

Abstract: The effects of decreased dietary sodium content during pregnancy and lactation on the activity of adrenal glands of the offspring were investigated. Low salt diet (0.3% of NaCl) increased the aldosterone production in newborn rats, on day 7 and on day 15 decreased the production of 18-hydroxydeoxycorticosterone only; on day 20 only the aldosterone production was increased. Based on the measurements of sodium and potassium concentrations in milk and urine of the offspring, the lasting effects of intrauterine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Although we did not measure the concentration of sodium in milk from lactating rats, previous studies have reported that an LS diet reduced sodium levels in milk. 42,43 HS and LS diets may influence organ development when administered during pregnancy, with reports of reduced nephron number and a predisposition to hypertension later in life in neonates. 36 Our study was designed to minimize these effects with the administration of LS to mothers before birth rather than at the beginning of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not measure the concentration of sodium in milk from lactating rats, previous studies have reported that an LS diet reduced sodium levels in milk. 42,43 HS and LS diets may influence organ development when administered during pregnancy, with reports of reduced nephron number and a predisposition to hypertension later in life in neonates. 36 Our study was designed to minimize these effects with the administration of LS to mothers before birth rather than at the beginning of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sodium concentration in the milk does not vary with maternal salt intake. The dams maintain normal levels of sodium in the milk by mobilization of sodium from bones and muscles (7,35). In view of this limited sodium intake and physiological requirement for sodium conservation for optimal growth, the young rats are in a state of relative volume depletion, which is reflected by an activated reninangiotensin system (RAS) (31,38,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Both sodium and potassium levels in the milk of rats can be altered by feeding them a low-salt or a high-salt diet (Dlouha et al, 1973;Vijande et al, 1996). When a high-salt diet (about 13%) was fed to pregnant ewes there was no change in the sodium concentration in their milk but, chloride levels in the milk increased (Meyer and Weir, 1954).…”
Section: Introductionmentioning
confidence: 99%